Paint‐On Epidermal Electronics for On‐Demand Sensors and Circuits. (30th November 2020) - Lin, Lancy; Dautta, Manik; Hajiaghajani, Amirhossein; Escobar, Alberto Ranier; Tseng, Peter; Khine, Michelle
Abstract: Wearable sensors continually evolve to become more epidermal‐like, yet still face challenges pertaining to conformability and reliance on wires and power sources. Herein, a nontoxic silver conductive ink made from children's school glue is used as a versatile medium for rapid, on‐demand wearable sensor development. This conductive ink can be painted directly onto the skin and to achieve dry electronics with maximal skin contact suitable for electrocardiogram use. Multilayer pressure sensors and near‐field communication (NFC) resonators manufactured using the silver ink demonstrate wireless and battery‐free capabilities for physiological monitoring purposes. Abstract : Silver ink made from Elmer's school glue exhibits high electrical conductivity and is suitable for the versatile and rapid fabrication of wearable sensors and electronics. The nontoxic formula can be directly painted onto skin to generate on‐demand dry electrodes and circuitry. Multilayer pressure sensors and near‐field communication (NFC) resonators demonstrate wireless and battery‐free capabilities for physiological monitoring needs.